2017
DOI: 10.1016/j.jtcvs.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Transaortic edge-to-edge mitral valve repair for moderate secondary/functional mitral regurgitation in patients undergoing aortic root/valve intervention

Abstract: Transaortic edge-to-edge mitral valve repair is a safe and effective technique to abolish secondary/functional mitral regurgitation. However, its impact on overall survival needs to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…[4,5,8,9,16,17] Currently, several studies have been published regarding the transaortic mitral repair technique in patients underwent AVR. [18][19][20] Nevertheless, Frederick and Woo [18] reported only seven patients; however, their results are consistent with our findings. In their study, all patients survived the immediate postoperative period with 100% survival at 30 days.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[4,5,8,9,16,17] Currently, several studies have been published regarding the transaortic mitral repair technique in patients underwent AVR. [18][19][20] Nevertheless, Frederick and Woo [18] reported only seven patients; however, their results are consistent with our findings. In their study, all patients survived the immediate postoperative period with 100% survival at 30 days.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, they concluded that transaortic edge-to-edge repair for ≥2+ functional MR could be safely performed during AVR and was associated with improvements in MR grade, pulmonary hemodynamics parameters, and left ventricular remodeling. [19] In addition, Choudhary et al [20] reported 16 patients who had moderate-to-severe MR and underwent aortic valve/root interventions. However, in their study, all patients had AI and the etiology and methodology were different from our study.…”
Section: Discussionmentioning
confidence: 99%
“…This double-orifice mitral valve repair technique has been used in diverse morphologic settings by several groups with satisfactory perioperative and midterm outcomes. 21 , 22 , 23 Nowadays, the concept is used by percutaneous interventional techniques like MitraClip implantation, especially in high-risk patients, were a reduction in regurgitation but not a perfectly competent valve is the primary goal, showing good results in the setting of the secondary mitral regurgitation. 1 , 2 , 3 In 2006, we began applying the edge-to-edge repair through a transventricular and transaortic route in high-risk patients requiring left ventricular remodeling or a challenging aortic root/valve surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Transventricular or transaortic mitral edge-to-edge repair represents a quick and safe alternative once the mitral valve can be approached from the surgical access way of the primary procedure. 21 , 22 , 23 Frequently dilated left ventricle and aortic root makes visibility of mitral valve easer. In the current study, we present our midterm experience with this procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation